Controversies in Teaching English Grammar - Singh, Renu (Academic Voices: A Multidisciplinary Journal, 2011)
Although grammar has long been taught and learnt, it has , recently, been a matter of debate whether it is worth to teach for language development. This article presents the controversies regarding teaching English grammar home and abroad. Additionally, it also overviews various trends in grammar teaching. Keywords Grammar, behaviourism, learning, acquisition, explicit, implicit DOI: http://dx.doi.org/10.3126/av.v1i0.5312 Academic Voices 2011; 1: 56-60